An electro-thermally activated rotary micro-positioner for slider-level dual-stage positioning in hard disk drives - Lau, Gih Keong (2016)
Slider-level micro-positioners are useful to assist a voice coil motor to perform fine head positioning over a Tb/in2 magnetic disk. Recently, a new kind of slider-level micro-positioner was developed using the thermal unimorph of the Si/SU8 composite. It has the advantages of a very small footprint and high mechanical resonant frequency, but its stroke generation is inadequate, with a 50 nm dynamic stroke at 1 kHz. There is a need for a larger thermally induced stroke. This paper presents a rotary design of an electrothermal micro-positioner to address the stroke requirements without consuming more power or decreasing the mechanical resonant frequency. Experimental studies show the present rotary design can produce a six-fold larger displacement, as compared to the previous lateral design, while possessing a 35 kHz resonant frequency. In addition, simple analytical models were developed to estimate: (i) the rotational stiffness and system's natural frequency, (ii) thermal unimorph bending and stage rotation, and (iii) the system's thermal time constant for this rotary electro-thermal micro-positioner. This study found that this rotary electro-thermal micro-positioner can meet the basic stroke requirement and high mechanical resonant frequency for a moving slider, but its thermal cut-off frequency needs to be increased further.